EVALUASI IMPLEMENTASI KAWASAN TANPA ROKOK PADA TEMPAT PROSES BELAJAR MENGAJAR DI KOTA AMBON - Latukarlutu, Frids; Hartono, Risky Kusuma (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
Smoking habits among adolescents pose a serious challenge to tobacco control efforts in Indonesia. As a preventive measure, the Ambon City Government enacted Regional Regulation No. 4 of 2020 concerning Smoke-Free Areas (SFA). However, its implementation in educational institutions has not been optimal. This study aims to analyze the implementation of the SFA policy in primary and secondary schools in Ambon City using George Edward III’s policy implementation framework, which includes communication, resources, disposition, and bureaucratic structure. This research employed a qualitative descriptive method with a case study approach. Data were collected through observations and semi-structured interviews with school principals, teachers, students, public health center officers, and health office personnel. Data analysis was conducted using the interactive model by Miles and Huberman. The findings indicate that the implementation of the SFA policy remains symbolic and relies heavily on individual initiative, lacking systemic support. Key obstacles include inconsistent policy communication, limited resources, low implementer commitment, and the absence of standardized operational procedures in schools. Nevertheless, strategic opportunities exist through the revision of regional regulations, budgetary support, and the integration of religious values in faith-based private schools. Inconsistent policy communication, limited resources, low implementer disposition in several schools, and weak bureaucratic structures are the primary obstacles. Although examples of good practices exist, particularly in faith-based private schools, overall SFA policy implementation in schools has yet to be optimize ABSTRAKKebiasaan merokok pada remaja menjadi tantangan serius dalam pengendalian tembakau di Indonesia. Sebagai upaya pencegahan, Pemerintah Kota Ambon menetapkan Peraturan Daerah No. 4 Tahun 2020 tentang Kawasan Tanpa Rokok (KTR), namun implementasinya di satuan pendidikan belum berjalan optimal. Penelitian ini bertujuan untuk menganalisis pelaksanaan kebijakan KTR di sekolah dasar dan menengah di Kota Ambon dengan menggunakan kerangka implementasi George Edward III, yang mencakup aspek komunikasi, sumber daya, disposisi, dan struktur birokrasi. Studi ini menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara semi-terstruktur dengan kepala sekolah, guru, siswa, serta petugas puskesmas, dan petugas dinas kesehatan. Analisis data dilakukan dengan pendekatan interaktif menurut Miles dan Huberman. Hasil penelitian menunjukkan bahwa pelaksanaan KTR masih bersifat simbolis dan bergantung pada inisiatif individu, tanpa dukungan sistemik yang kuat. Hambatan utama terletak pada komunikasi kebijakan yang tidak konsisten, keterbatasan sumber daya, rendahnya komitmen pelaksana, serta belum adanya prosedur operasional yang baku di sekolah. Meskipun demikian, terdapat peluang strategis melalui revisi peraturan daerah, dukungan anggaran, serta nilai-nilai religius di sekolah swasta berbasis agama. komunikasi kebijakan yang tidak konsisten, keterbatasan sumber daya, rendahnya disposisi pelaksana di sebagian sekolah, serta lemahnya struktur birokrasi menjadi penghambat utama. Meskipun terdapat praktik baik, khususnya di sekolah swasta berbasis nilai agama, secara umum pelaksanaan KTR belum optimal.